Immunogenicity and reactivity of recombinant Zika virus NS1 inclusion bodies from an Indonesian isolate - UTAMI MULYANINGRUM; YANRI WIJAYANTI SUBRONTO; DWI ARIS AGUNG NUGRAHANINGSIH; NASTITI WIJAYANTI (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Mulyaningrum U, Subronto YW, Nugrahaningsih DAA, Wijayanti N. 2024. Immunogenicity and reactivity of recombinant Zika virus NS1 inclusion bodies from an Indonesian isolate. Biodiversitas 25: 2028-2034. Zika virus (ZIKV) still poses a significant global health hazard, with the potential for its dissemination to additional nations and the re-emergence of epidemics in previously impacted regions. Proper laboratory testing during surveillance can prevent future outbreaks. Non-Structural 1 (NS1) protein has been identified as a promising biomarker for detecting ZIKV infection. Therefore, this study produces and assesses the immunogenicity of the full-length recombinant ZIKV NS1 protein (rNS1FL) from an Indonesian isolate. It also studies its reactivity against other flavivirus members, especially the Dengue Virus (DENV). The cDNA fragment comprising the ZIKV NS1 sequence was synthesized and cloned into the pET28a plasmid. Subsequently, the recombinant plasmid was introduced into BL21(DE3)-competent Escherichia coli cells, and the protein was purified through affinity chromatography. Female BALB/c mice (Mus musculus) were intraperitoneally immunized with purified rNS1FL. An Enzyme-Linked Immunosorbent Assay (ELISA) evaluates the immunogenicity of rNS1FL and its cross-reactivity with the DENV NS1 monoclonal antibody. rNS1FL protein was expressed as insoluble fractions (inclusion bodies) at the expected size of approximately 48 kDa. The ELISA showed that immunization of BALB/c mice with purified rNS1FL from inclusion bodies led to a substantial triggering of NS1-specific antibodies. Furthermore, the test also revealed limited recognition of rNS1FL by the DENV NS1 monoclonal antibody. The findings indicated that rNS1FL inclusion bodies have immunogenic solid properties and did not display any cross-reactivity with the DENV NS1 monoclonal antibody. These observations showed the potential of rNS1FL as a serological diagnostic material for detecting ZIKV infection.